Asesmen Formatif pada Mata Pelajaran PAI dan Budi Pekerti di SMK Al-Munawarroh Cilacap - Nasuhah, Fadilah; Rohmad (Sekolah Tinggi Agama Islam (STAI) AL-IKHLAS DAIRI SIDIKALANG, 2025)
Formative assessment plays a crucial role in learning because it functions as an assessment to monitor and improve learning. The PAI BP material aims to realize the values of Islam rahmatan lil’alamin in the learning process, and the achievement of this goal is carried out through a process known as formative assessment, which plays a supportive role in that process. Therefore, formative assessment is necessary to meet the learning needs of students and to understand the level of student development in the learning process, which does not solely focus on the final outcome. Thus, the implementation of formative assessment in the PAI BP subject is very necessary. This study aims to describe the implementation of formative assessment in the PAI BP subject at SMK Al-Munawarroh Cilacap. This research is a type of field study using a descriptive qualitative approach with data collection techniques through interviews, documentation gathering, and triangulation. This formative assessment research is focused on the X Accounting and X TKJ classes at SMK Al-Munawarroh Cilacap. Meanwhile, the data analysis techniques used are data reduction, data presentation, and conclusion drawing. The results of this study are: the implementation of formative assessment in the PAI BP subject at SMK Al-Munawarroh Cilacap is carried out in each chapter with several stages, namely the planning stage, implementation, and follow-up or feedback. In each of these stages, a variety of techniques were used in the form of assessments, namely observation, memorization, oral exams, practice, and product presentations.